STUDY OF THE IMPACT OF SEAWEED BUSINESS DEVELOPMENT ON COASTAL COMMUNITY EMPOWERMENT (CASE STUDY: CORPORATE SOCIAL RESPONSIBILITY PROGRAM OF PT. BHUMI JATI POWER IN JEPARA DISTRICT, CENTRAL JAVA PROVINCE) - Cocon, Cocon; Saputra, Ari Wibawa Nurma; Prabowo, Handoko Agung; Azizah, Nur; Martha, Marlia Chandra; Fuad, Noor Azharul; Mustagfirin, Mustagfirin (Universitas Mataram, 2025)
The potential of fishery resources in Jepara Regency is quite large, especially for the development of fisheries cultivation, however the level of welfare of the coastal community of Jepara which is still minimal, in addition to the lack of development of cultivation development centers that are able to drive the local economy based on superior commodities. The objectives of this study are: (1) to conduct a study of the impact of seaweed business development through the CSR program on the empowerment of the coastal community of Jepara; (2) to assess the sustainability status of the seaweed business development program; and (3) to determine effective strategies for the sustainability of the seaweed business. The research method is carried out through a quantitative and qualitative descriptive approach. The impact study is carried out through scoring with a Likert scale approach to the variables of empowerment aspects, while the assessment of sustainability status is carried out through a multidimensional scaling (MDS) approach with the Rap-Fish ordination technique. The study was conducted in Bondo Village, Bangsri District, Jepara Regency from 2-14 December 2024. The results of the data analysis concluded that the CSR program for developing seaweed businesses had a positive impact on aspects of community empowerment, especially in aspects of production and the environment, economic aspects and social-institutional aspects. Meanwhile, the results of the sustainability analysis showed that this program has a sustainable category with an index value of 86.25. The strategy that needs to be intervened in the long term is an aggressive strategy, namely focusing more on optimization efforts in encouraging existing strengths and utilizing opportunities to boost business development performance